Modelling of cardiac biventricular electromechanics with coronary blood flow to investigate the influence of coronary arterial motion on coronary haemodynamic - Laila Fadhillah, Ulta Delestri; Al Abed, Amr; Dokos, Socrates; Mohd Jamil, Mohamed Mokhtarudin; Kok, Foo Ngai; Bressloff, Neil W.; Sengers, Bram G; Azam, Ahmad Bakir (Elsevier Ireland Ltd, 2025)
Background and objective Coronary flow is strongly influenced by the geometry and motion of coronary arteries, which change periodically in response to myocardial contraction throughout the cardiac cycle. However, a computational framework integrating cardiac biventricular electromechanics with dynamic coronary artery flow using a simplified, yet comprehensive mathematical approach remains underexplored. This study aims to develop a coupled 3D model of cardiac biventricular electromechanics and coronary circulation, enabling simulation of the interplay between cardiac electrical activity, mechanical function and coronary flow.